‘Jon Jon’ Magnolia: A Late-Flowering Deciduous Magnolia for Northern Florida - Gary W. Knox (EDIS)
This large-flowered, hybrid, deciduous magnolia flowers profusely in late spring, about two weeks after most saucer magnolias, but before foliage emerges. This allows ‘Jon Jon’ to miss spring freezes that often damage saucer and other spring-flowering magnolias. This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, October 2011.